2000
DOI: 10.1038/sj.ijo.0801361
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic status and soluble tumor necrosis factor receptor levels in relation to plasma leptin concentrations among normal weight and overweight US men

Abstract: OBJECTIVE: Leptin, an adipocyte-derived protein product of the obesity (ob) gene, is a multifunctional polypeptide associated with the development of obesity-related disorders in humans. There is considerable inter-individual variation in plasma leptin even among subjects with comparable obesity levels, which suggests that factors other than adipose mass may be involved in the regulation of leptin expression andaor production. The purpose of this study was to evaluate the potential role of glycemic status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 69 publications
2
22
2
2
Order By: Relevance
“…Interestingly, the positive association between TNF-␣R2 was more evident in nonobese than obese women. This result is consistent with previous findings that TNF-␣R2 was more strongly correlated with leptin, insulin, and C-peptide among normal weight than overweight subjects (41).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the positive association between TNF-␣R2 was more evident in nonobese than obese women. This result is consistent with previous findings that TNF-␣R2 was more strongly correlated with leptin, insulin, and C-peptide among normal weight than overweight subjects (41).…”
Section: Discussionsupporting
confidence: 83%
“…18 In contrast to this study, the patients in our other study were young, had normal renal function, did not have proteinuria, and were not obese. Although some reports demonstrated that TNFRs may be related to those clinical characteristics, 20 our two studies indicate that the concentrations of TNFR1 and TNFR2 are not markedly influenced by these clinical covariates. Moreover, they are a stable patient characteristic as demonstrated in our other work.…”
Section: Discussionmentioning
confidence: 82%
“…C-peptide is often used in such settings because C-peptide levels are thought to be less variable than insulin. C-peptide levels do, however, substantially increase postprandially (11), and there is an imperfect correlation of C-peptide and insulin even when measured in fasting specimens (12). Therefore, although recent prospective studies of C-peptide have provided important data, their findings have been inconsistent (13)(14)(15)(16)(17), and direct measurement of insulin, the putative carcinogenic agent, may provide a more accurate estimation of the relation of hyperinsulinemia with colorectal cancer.…”
Section: Introductionmentioning
confidence: 82%